Pengaruh Konsumsi Jus Buah Bit Lemon dengan Tablet Fe terhadap Peningkatan Kadar Hemoglobin Ibu Hamil Trimester III di Kota Semarang - Fitriyani Indah Lestari; Qomariyah Qomariyah; Nella Vallen I.P (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Anemia in pregnancy increases the risk of maternal and fetal morbidity and mortality, with a higher incidence in the third trimester. Although Fe tablets serve as the main therapy, non-pharmacological alternatives such as beetroot and lemon juice also have the potential to raise hemoglobin levels. Objective: To determine the effect of consuming beetroot-lemon juice combined with Fe tablets on hemoglobin levels in third-trimester pregnant women in Semarang. Method: This study applied a quasi-experimental design with a two-group pre-test post-test approach, allowing the measurement of hemoglobin level changes before and after the intervention. The study population consisted of all pregnant women in their third trimester, with gestational ages between 32 and 38 weeks, registered at two community health centers: PMB Puji Widiastuti, Amd.Keb, with 16 anemic respondents, and PMB Ika Febri Setyaning Astuti, Str.Keb, with 15 anemic respondents. A total of 31 respondents were obtained using total sampling. Data collection was conducted through observation sheets, and analysis was performed using the Mann Whitney statistical test. Results: The intervention group, which consumed beetroot and lemon juice along with Fe tablets, achieved a Mean Rank of 13.41, whereas the control group recorded a Mean Rank of 18.77, with an effectiveness difference of 5.36. Statistical analysis yielded a p-value of 0.048, indicating a significant difference between the groups. In conclusion, the combination of beetroot and lemon juice with Fe tablets effectively increased hemoglobin levels among third-trimester pregnant women with anemia. This finding suggests that such combination therapy can serve as a valuable alternative in the management of anemia during pregnancy.